Relative Effectiveness of Print and Digital Advertising: A Memory Perspective. (October 2021) - Venkatraman, Vinod; Dimoka, Angelika; Vo, Khoi; Pavlou, Paul A.
The exponential growth in digital media has recently challenged the value of print media in the overall marketing mix. Across three studies, the authors evaluate the relative effectiveness of print ads versus digital ads. In Study 1, using eye tracking and biometric measures during exposure, the authors find stronger encoding and engagement for print ads over digital ads. A week later, participants showed no significant difference in recognizing ads across format, though they better remembered the encoding context of print ads. Notably, using functional magnetic resonance imaging, the authors find greater activation in hippocampus and parahippocampal regions for print ads relative to digital ads. Extending these insights, Study 2 demonstrates that participants better remember print ads across contents, context, and brand associations when using snippets as retrieval cues. In addition to establishing the robustness of previous findings, Study 3 provides further evidence that the observed memory advantage for print ads is primarily due to superior encoding during initial exposure. From a practical perspective, these findings suggest that marketers should not discount the value of print media in advertising, despite the rapid growth of digital media and communications.